Flame-retardant wear-resistant NBR rubber compound and preparation method thereof

By using ore powder instead of part of talc powder as filler, combined with specific components and processes, flame-retardant and wear-resistant NBR kneaded glue is prepared, which solves the problem of high costs in the existing technology, achieves cost reduction and performance maintenance, and meets environmental protection requirements.

CN120289884APending Publication Date: 2025-07-11GUANGDONG GUANJU NEW MATERIAL TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510446000.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-10
Publication Date
2025-07-11

AI Technical Summary

Technical Problem

Existing flame retardant wear-resistant NBR kneading materials usually use high-priced silicates such as talc and silica as fillers, resulting in excessive production costs.

Method used

The flame-retardant and wear-resistant NBR kneaded glue is prepared through a specific kneading process by using mineral powder instead of part of the talc powder as filler, and combined with carbon black, plasticizer, flame retardant, vulcanizer and anti-aging agent.

Benefits of technology

The preparation cost is significantly reduced without affecting performance, and the use of ore powder to achieve resource reuse, reduce the risk of heavy metals, improve processing performance, reduce the risk of mixing and sticky rollers, increase fluidity and thermal conductivity, and shorten the mixing time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005352612530000071
    Figure BDA0005352612530000071
Patent Text Reader

Abstract

The invention discloses a flame-retardant wear-resistant NBR rubber compound and a preparation method thereof, and relates to the technical field of rubber compounds, the flame-retardant wear-resistant NBR rubber compound comprises a rubber matrix, carbon black, a filler, a plasticizer and assistants, the rubber matrix is specifically nitrile rubber, and the assistants are specifically a flame retardant, a vulcanizing agent, an accelerant and an anti-aging agent. The mineral powder is used for replacing part of talcum powder to serve as filler of the flame-retardant and wear-resistant NBR rubber compound, under the condition that the performance of the flame-retardant and wear-resistant NBR rubber compound is not affected, the production cost of the flame-retardant and wear-resistant NBR rubber compound is remarkably reduced, meanwhile, resource utilization can be achieved through the mineral powder, the risk of heavy metal is low, the environmental requirements for environmental protection and sustainable development are met, and the flame-retardant and wear-resistant NBR rubber compound is suitable for industrial production. The mineral powder can improve the processability of the rubber compound, has more regular mineral powder particles, reduces the risk of roller sticking during mixing, increases the fluidity of the rubber compound, has better thermal conductivity than talcum powder, has more stable temperature during internal mixing, has better compatibility with carbon black, and can shorten the mixing time by about 10%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of rubber compounds, and specifically relates to a flame-retardant and wear-resistant NBR rubber compound and a preparation method thereof. Background Art

[0002] An NBR (nitrile butadiene rubber) rubber compound is an elastic material prepared from nitrile butadiene rubber as the base material, adding fillers, additives, cross-linking agents and other components through processes such as mixing, kneading and vulcanization. NBR is widely used in the fields of the automotive industry, mechanical equipment and consumer goods due to its excellent oil resistance and wear resistance.

[0003] The Chinese invention patent with the authorization announcement number CN110643089A discloses an NBR rubber compound for a flame-retardant and wear-resistant conveyor belt cover layer, which is composed of the following components in weight percentages: nitrile butadiene rubber: 35-40%, polyvinyl chloride 8-10%, reinforcing filler 25-30%, softening agent 3-8%, anti-aging agent 0.3-0.8%, compounding agent 20-25%, vulcanization accelerator 1-2%. The product of the present invention has good flame-retardant, wear-resistant and oil-resistant properties, and has good processing properties and physical and mechanical properties;

[0004] In the above-mentioned patent, the flame-retardant and wear-resistant NBR rubber compound material usually uses silicates as fillers, such as talcum powder and silica, which usually have a relatively high price, especially in the case of high purity and fineness. In the rubber compound formula, the dosage of silicates is large, and the cost of preparing the flame-retardant and wear-resistant NBR rubber compound is too high. Summary of the Invention

[0005] The purpose of the present invention is to provide a flame-retardant and wear-resistant NBR rubber compound and a preparation method thereof, which solve the problem that the existing flame-retardant and wear-resistant NBR rubber compound materials usually use silicates as fillers, such as talcum powder and silica, which usually have a relatively high price, especially in the case of high purity and fineness. In the rubber compound formula, the dosage of silicates is large, and the cost of preparing the flame-retardant and wear-resistant NBR rubber compound is too high.

[0006] The present invention solves the above technical problems through the following technical solutions. A flame-retardant and wear-resistant NBR rubber compound includes a rubber matrix, carbon black, a filler, a plasticizer and additives.

[0007] Preferably, the rubber base material is specifically nitrile butadiene rubber, and the additives are specifically a flame retardant, a vulcanizing agent, an accelerator and an anti-aging agent.

[0008] Preferably, the filler is specifically talcum powder, the weight ratio of nitrile rubber is 65% - 75%, the weight ratio of carbon black is 18% - 25%, the weight ratio of talcum powder is 12% - 18%, the weight ratio of plasticizer is 6% - 10%, the weight ratio of flame retardant is 5% - 8%, the weight ratio of vulcanizing agent is 1.5% - 2%, the weight ratio of accelerator is 1% - 1.5%, and the weight ratio of antioxidant is 1% - 1.5%.

[0009] Preferably, the filler is specifically ore powder, the weight ratio of nitrile rubber is 65% - 75%, the weight ratio of carbon black is 18% - 25%, the weight ratio of ore powder is 12% - 18%, the weight ratio of plasticizer is 6% - 10%, the weight ratio of flame retardant is 5% - 8%, the weight ratio of vulcanizing agent is 1.5% - 2%, the weight ratio of accelerator is 1% - 1.5%, and the weight ratio of antioxidant is 1% - 1.5%.

[0010] Preferably, the filler is specifically a mixture of talcum powder and ore powder, the weight ratio of nitrile rubber is 65% - 75%, the weight ratio of carbon black is 18% - 25%, the weight ratio of the mixture is 12% - 18%, the weight ratio of plasticizer is 6% - 10%, the weight ratio of flame retardant is 5% - 8%, the weight ratio of vulcanizing agent is 1.5% - 2%, the weight ratio of accelerator is 1% - 1.5%, and the weight ratio of antioxidant is 1% - 1.5%.

[0011] A preparation method of a flame - retardant and wear - resistant NBR masterbatch includes the following steps:

[0012] Step S1, raw material preparation: Prepare the required nitrile rubber, carbon black, talcum powder, plasticizer, flame retardant, vulcanizing agent, accelerator and antioxidant according to the weight ratio;

[0013] Step S2, raw material pretreatment: Dry the talcum powder to make its moisture content ≤ 0.5%, treat it with silane coupling agent KH - 550 in a high - speed mixer for 10 minutes, and thin - pass the nitrile rubber 3 times on an open mill for plasticizing;

[0014] Step S3, the first - stage mixing: In a Banbury mixer, adjust the rotation speed to 40 rpm, add the plasticized nitrile rubber and preheat it to 60°C, add the plasticizer and antioxidant, mix for two minutes, add the flame retardant, add the carbon black, mix until the power curve is stable, add the treated talcum powder in two batches, discharge the rubber after mixing, press the masterbatch into a 5 - mm - thick sheet, and store it at room temperature for 24 hours;

[0015] Step S4, the second - stage mixing: On an open mill, adjust the roll gap to 1 mm and the roll temperature to 45°C, thin - pass the masterbatch 3 times, alternately add the vulcanizing agent and accelerator, mix for 5 minutes, adjust the roll gap to 2 mm, and turn and knead it in a triangular wrap 6 times, then take off the sheet after completion;

[0016] Step S5, Quality Inspection: Conduct physical property tests on the finished product, including tensile strength, flame retardancy, and abrasion resistance, to ensure that the material meets the requirements.

[0017] Preferably, a method for preparing a flame-retardant and wear-resistant NBR masterbatch includes the following steps:

[0018] Step V1, Raw Material Preparation: Prepare the required nitrile rubber, carbon black, mineral powder, plasticizer, flame retardant, vulcanizing agent, accelerator, and antioxidant according to the weight ratio;

[0019] Step V2, Raw Material Pretreatment: Dry the mineral powder to make its moisture content ≤ 0.3%, modify it with a titanate coupling agent NDZ-201 in a high-speed mixer for 10 minutes, and thin-pass the nitrile rubber 3 times on an open mill for plasticization;

[0020] Step V3, First-stage Mixing: In an internal mixer, adjust the rotation speed to 40 rpm and the initial temperature to 60 °C. Add the plasticized nitrile rubber and preheat it to the state of wrapping the roll. Add the plasticizer and antioxidant, mix for two minutes, add the flame retardant, add the carbon black, mix until the power curve is stable, add the treated mineral powder in two batches, discharge the rubber after mixing, press the masterbatch into a sheet with a thickness of 5 mm, and store it at room temperature for 24 hours;

[0021] Step V4, Second-stage Mixing: On an open mill, adjust the roll gap to 1 mm and the roll temperature to 45 °C. Thin-pass the masterbatch 3 times, alternately add the vulcanizing agent and accelerator, mix for 6 minutes, adjust the roll gap to 2 mm, and turn and mix in a triangular wrap 6 times, then take off the sheet after completion;

[0022] Step V5, Quality Inspection: Conduct physical property tests on the finished product, including tensile strength, flame retardancy, and abrasion resistance, to ensure that the material meets the requirements.

[0023] Preferably, a method for preparing a flame-retardant and wear-resistant NBR masterbatch includes the following steps:

[0024] Step N1, Raw Material Preparation: Prepare the required nitrile rubber, carbon black, talc powder, mineral powder, plasticizer, flame retardant, vulcanizing agent, accelerator, and antioxidant according to the weight ratio;

[0025] Step N2, Raw Material Pretreatment: Dry the talc powder, treat it with a silane coupling agent KH-550 in a high-speed mixer for 10 minutes, dry the mineral powder, modify it with a titanate coupling agent NDZ-201 in a high-speed mixer for 10 minutes, and thin-pass the nitrile rubber 3 times on an open mill for plasticization;

[0026] Step N3, First-stage mixing: In a Banbury mixer, adjust the rotational speed to 40 rpm and the initial temperature to 60°C. Add the plasticized nitrile rubber and preheat it until it wraps around the rolls. Then add the plasticizer and antioxidant, mix for two minutes, add the flame retardant, add the carbon black, and mix until the power curve is stable. Add the mixture of talc powder and mineral powder in two batches, discharge the rubber after mixing, press the masterbatch into a sheet 5 mm thick, and let it stand at room temperature for 24 hours.

[0027] Step N4, Second-stage mixing: In an open mill, adjust the roll gap to 0.8 mm and the roll temperature to 45°C. Thin-pass the masterbatch 3 times, alternately add the vulcanizing agent and accelerator, mix for 5 minutes, adjust the roll gap to 2 mm, and turn and knead it in a triangular wrap 6 times. Then take off the sheet after completion.

[0028] Step N5, Quality inspection: Conduct physical property tests on the finished product, including tensile strength, flame retardancy, and abrasion resistance, to ensure that the material meets the requirements.

[0029] The beneficial effects of the present invention compared with the prior art are as follows:

[0030] In the present invention, by using mineral powder to replace part of the talc powder as the filler of the flame-retardant and wear-resistant NBR masterbatch, without affecting the performance of the flame-retardant and wear-resistant NBR masterbatch, the production cost of the flame-retardant and wear-resistant NBR masterbatch is significantly reduced. At the same time, the use of mineral powder can achieve resource utilization, with low heavy metal risk, meeting the environmental requirements of environmental protection and sustainable development. Mineral powder can improve the processing performance of the masterbatch. The mineral powder particles are more regular, reducing the risk of sticking to the rolls during mixing, increasing the fluidity of the rubber compound. The thermal conductivity of the mineral powder is better than that of talc powder, making the temperature more stable during the Banbury mixing process. The compatibility between the mineral powder and carbon black is better, and the mixing time can be shortened by about 10%. Specific embodiments

[0031] A more detailed description is given of the above and other technical features and advantages of the present invention.

[0032] A flame-retardant and wear-resistant NBR masterbatch includes a rubber matrix, carbon black, filler, plasticizer, and additives. The rubber base material is specifically nitrile rubber, and the additives are specifically flame retardant, vulcanizing agent, accelerator, and antioxidant.

[0033] Further, the filler is specifically talc powder. The weight ratio of nitrile rubber is 65% - 75%, the weight ratio of carbon black is 18% - 25%, the weight ratio of talc powder is 12% - 18%, the weight ratio of plasticizer is 6% - 10%, the weight ratio of flame retardant is 5% - 8%, the weight ratio of vulcanizing agent is 1.5% - 2%, the weight ratio of accelerator is 1% - 1.5%, and the weight ratio of antioxidant is 1% - 1.5%.

[0034] Further, the filler is specifically mineral powder, the weight ratio of nitrile rubber is 65% - 75%, the weight ratio of carbon black is 18% - 25%, the weight ratio of mineral powder is 12% - 18%, the weight ratio of plasticizer is 6% - 10%, the weight ratio of flame retardant is 5% - 8%, the weight ratio of vulcanizing agent is 1.5% - 2%, the weight ratio of accelerator is 1% - 1.5%, and the weight ratio of antioxidant is 1% - 1.5%.

[0035] Further, the filler is specifically a mixture of talc powder and mineral powder, the weight ratio of nitrile rubber is 65% - 75%, the weight ratio of carbon black is 18% - 25%, the weight ratio of the mixture is 12% - 18%, the weight ratio of plasticizer is 6% - 10%, the weight ratio of flame retardant is 5% - 8%, the weight ratio of vulcanizing agent is 1.5% - 2%, the weight ratio of accelerator is 1% - 1.5%, and the weight ratio of antioxidant is 1% - 1.5%.

[0036] Example 1

[0037] This example provides a technical solution: a flame-retardant and wear-resistant NBR masterbatch, including nitrile rubber, carbon black, talc powder, plasticizer, flame retardant, vulcanizing agent, accelerator and antioxidant, among which there are 650 g of nitrile rubber, 180 g of carbon black, 120 g of talc powder, 80 g of plasticizer, 80 g of flame retardant, 18 g of vulcanizing agent, 12 g of accelerator and 15 g of antioxidant;

[0038] It is prepared through the following preparation steps:

[0039] Step S1, raw material preparation: Prepare 650 g of nitrile rubber, 180 g of carbon black, 120 g of talc powder, 80 g of plasticizer, 80 g of flame retardant, 18 g of vulcanizing agent, 12 g of accelerator and 15 g of antioxidant according to the weight ratio;

[0040] Step S2, raw material pretreatment: Dry the talc powder to make its moisture content ≤ 0.5%, treat it with silane coupling agent KH-550 in a high-speed mixer for 10 minutes, and thin-pass the nitrile rubber 3 times on an open mill for plasticization;

[0041] Step S3, the first-stage mixing: In an internal mixer, adjust the rotation speed to 40 rpm, add the plasticized nitrile rubber and preheat it to 60 °C, add the plasticizer and antioxidant, mix for two minutes, add the flame retardant, add the carbon black, mix until the power curve is stable, add the treated talc powder in two batches, discharge the rubber after mixing, press the masterbatch into a 5-mm-thick sheet, and store it at room temperature for 24 hours;

[0042] Step S4, the second-stage mixing: On an open mill, adjust the roll gap to 1 mm and the roll temperature to 45 °C, thin-pass the masterbatch 3 times, alternately add the vulcanizing agent and accelerator, mix for 5 minutes, adjust the roll gap to 2 mm, and turn and knead it in a triangular wrap 6 times, then take off the sheet after completion;

[0043] Step S5, Quality Inspection: Conduct physical property tests on the finished product, including tensile strength, flame retardancy, and abrasion resistance, to ensure that the material meets the requirements.

[0044] Example Two

[0045] This example provides a technical solution: A flame-retardant and wear-resistant NBR masterbatch, including nitrile rubber, carbon black, mineral powder, plasticizer, flame retardant, vulcanizing agent, accelerator, and antioxidant. Among them, there are 650 g of nitrile rubber, 180 g of carbon black, 120 g of mineral powder, 80 g of plasticizer, 80 g of flame retardant, 18 g of vulcanizing agent, 12 g of accelerator, and 15 g of antioxidant;

[0046] It is prepared through the following preparation steps:

[0047] Step V1, Raw Material Preparation: Prepare 650 g of nitrile rubber, 180 g of carbon black, 120 g of mineral powder, 80 g of plasticizer, 80 g of flame retardant, 18 g of vulcanizing agent, 12 g of accelerator, and 15 g of antioxidant according to the weight ratio;

[0048] Step V2, Raw Material Pretreatment: Dry the mineral powder to make its moisture content ≤ 0.3%, modify it with titanate coupling agent NDZ-201 in a high-speed mixer for 10 minutes, and thin-pass the nitrile rubber on an open mill 3 times for plasticization;

[0049] Step V3, First-stage Mixing: In an internal mixer, adjust the rotation speed to 40 rpm and the initial temperature to 60 °C. Add the plasticized nitrile rubber and preheat it to the state of wrapping around the roll. Add the plasticizer and antioxidant, mix for two minutes, add the flame retardant, add the carbon black, mix until the power curve is stable, add the treated mineral powder in two batches, mix and then discharge the rubber. Press the masterbatch into a sheet with a thickness of 5 mm and let it stand at room temperature for 24 hours;

[0050] Step V4, Second-stage Mixing: In an open mill, adjust the roll gap to 1 mm and the roll temperature to 45 °C. Thin-pass the masterbatch 3 times, alternately add the vulcanizing agent and accelerator, mix for 6 minutes, adjust the roll gap to 2 mm, and turn and knead it in a triangular shape 6 times. After completion, take off the sheet;

[0051] Step V5, Quality Inspection: Conduct physical property tests on the finished product, including tensile strength, flame retardancy, and abrasion resistance, to ensure that the material meets the requirements.

[0052] Example Three

[0053] This example provides a technical solution: A flame-retardant and wear-resistant NBR masterbatch, including nitrile rubber, carbon black, talc powder and mineral powder, plasticizer, flame retardant, vulcanizing agent, accelerator, and antioxidant. Among them, there are 650 g of nitrile rubber, 180 g of carbon black, 72 g of talc powder, 48 g of mineral powder, 80 g of plasticizer, 80 g of flame retardant, 18 g of vulcanizing agent, 12 g of accelerator, and 15 g of antioxidant;

[0054] It is prepared through the following preparation steps:

[0055] Step N1, raw material preparation: Prepare 650 g of nitrile rubber, 180 g of carbon black, 72 g of talc powder, 48 g of ore powder, 80 g of plasticizer, 80 g of flame retardant, 18 g of vulcanizing agent, 12 g of accelerator and 15 g of antioxidant according to the weight ratio;

[0056] Step N2, raw material pretreatment: Dry the talc powder, treat it with silane coupling agent KH-550 in a high-speed mixer for 10 minutes, dry the ore powder, modify it with titanate coupling agent NDZ-201 in a high-speed mixer for 10 minutes, and thin-pass the nitrile rubber 3 times on an open mill for plasticizing;

[0057] Step N3, first-stage mixing: In an internal mixer, adjust the rotation speed to 40 rpm and the initial temperature to 60 °C. Add the plasticized nitrile rubber and preheat it to the state of wrapping the roller. Add the plasticizer and antioxidant, mix for two minutes, add the flame retardant, add the carbon black, mix until the power curve is stable, add the mixture of talc powder and ore powder in two batches, discharge the rubber after mixing, press the masterbatch into a sheet with a thickness of 5 mm, and store it at room temperature for 24 hours;

[0058] Step N4, second-stage mixing: On an open mill, adjust the roll gap to 0.8 mm and the roll temperature to 45 °C. Thin-pass the masterbatch 3 times, alternately add the vulcanizing agent and the accelerator, mix for 5 minutes, adjust the roll gap to 2 mm, and turn and mix in a triangular wrap 6 times. After completion, take off the sheet;

[0059] Step N5, quality inspection: Conduct physical property tests on the finished product, including tensile strength, flame retardancy and abrasion resistance, to ensure that the material meets the requirements.

[0060] Example 4

[0061] This example provides a technical solution: A flame-retardant and wear-resistant NBR masterbatch, including nitrile rubber, carbon black, talc powder and ore powder, plasticizer, flame retardant, vulcanizing agent, accelerator and antioxidant, among which there are 650 g of nitrile rubber, 180 g of carbon black, 60 g of talc powder, 60 g of ore powder, 80 g of plasticizer, 80 g of flame retardant, 18 g of vulcanizing agent, 12 g of accelerator and 15 g of antioxidant;

[0062] It is prepared through the following preparation steps:

[0063] Step N1, raw material preparation: Prepare 650 g of nitrile rubber, 180 g of carbon black, 60 g of talc powder, 60 g of ore powder, 80 g of plasticizer, 80 g of flame retardant, 18 g of vulcanizing agent, 12 g of accelerator and 15 g of antioxidant according to the weight ratio;

[0064] Step N2, Raw material pretreatment: The talcum powder is dried, treated with silane coupling agent KH-550 in a high-speed mixer for 10 minutes, the ore powder is dried, and modified with titanate coupling agent NDZ-201 in a high-speed mixer for 10 minutes. The nitrile rubber is passed thinly through the open mill 3 times for plasticizing;

[0065] Step N3, First-stage mixing: In the internal mixer, adjust the rotation speed to 40 rpm and the initial temperature to 60 °C. Add the plasticized nitrile rubber and preheat it to the state of wrapping the roll. Add the plasticizer and antioxidant, mix for two minutes, add the flame retardant, add the carbon black, mix until the power curve is stable, add the mixture of talcum powder and ore powder in two batches, discharge the rubber after mixing, press the masterbatch into a sheet with a thickness of 5 mm, and store it at room temperature for 24 hours;

[0066] Step N4, Second-stage mixing: In the open mill, adjust the roll gap to 0.8 mm and the roll temperature to 45 °C. Pass the masterbatch thinly through the mill 3 times, alternately add the vulcanizing agent and accelerator, mix for 5 minutes, adjust the roll gap to 2 mm, and turn it over and knead it in a triangular shape 6 times. After completion, take off the sheet;

[0067] Step N5, Quality inspection: Conduct physical property tests on the finished product, including tensile strength, flame retardancy and abrasion resistance, to ensure that the material meets the requirements.

[0068] Example Five

[0069] This example provides a technical solution: A flame-retardant and wear-resistant NBR masterbatch, including nitrile rubber, carbon black, talcum powder, ore powder, plasticizer, flame retardant, vulcanizing agent, accelerator and antioxidant, among which there are 650 g of nitrile rubber, 180 g of carbon black, 48 g of talcum powder, 72 g of ore powder, 80 g of plasticizer, 80 g of flame retardant, 18 g of vulcanizing agent, 12 g of accelerator and 15 g of antioxidant;

[0070] It is prepared through the following preparation steps:

[0071] Step N1, Raw material preparation: Prepare 650 g of nitrile rubber, 180 g of carbon black, 48 g of talcum powder, 72 g of ore powder, 80 g of plasticizer, 80 g of flame retardant, 18 g of vulcanizing agent, 12 g of accelerator and 15 g of antioxidant according to the weight ratio;

[0072] Step N2, Raw material pretreatment: The talcum powder is dried, treated with silane coupling agent KH-550 in a high-speed mixer for 10 minutes, the ore powder is dried, and modified with titanate coupling agent NDZ-201 in a high-speed mixer for 10 minutes. The nitrile rubber is passed thinly through the open mill 3 times for plasticizing;

[0073] Step N3, First-stage mixing: In the internal mixer, adjust the rotation speed to 40 rpm and the initial temperature to 60 °C. Add the plasticized nitrile rubber and preheat it until it wraps around the roller. Then add the plasticizer and antioxidant, mix for two minutes, add the flame retardant, add the carbon black, and mix until the power curve is stable. Add the mixture of talc powder and mineral powder in two batches, discharge the rubber after mixing, press the masterbatch into a sheet with a thickness of 5 mm, and store it at room temperature for 24 hours;

[0074] Step N4, Second-stage mixing: In the open mill, adjust the roll gap to 0.8 mm and the roll temperature to 45 °C. Pass the masterbatch thinly through the rolls 3 times, alternately add the vulcanizing agent and accelerator, mix for 5 minutes, adjust the roll gap to 2 mm, and turn and knead it in a triangular wrap 6 times. After completion, take off the sheet;

[0075] Step N5, Quality inspection: Conduct physical property tests on the finished product, including tensile strength, flame retardancy, and abrasion resistance, to ensure that the material meets the requirements.

[0076] Take equal amounts of the flame-retardant and wear-resistant NBR masterbatch obtained in Example 1, the flame-retardant and wear-resistant NBR masterbatch obtained in Example 2, the flame-retardant and wear-resistant NBR masterbatch obtained in Example 3, the flame-retardant and wear-resistant NBR masterbatch obtained in Example 4, and the flame-retardant and wear-resistant NBR masterbatch obtained in Example 5, and use them in the operation. Detect their tensile strength, elongation at break, Akron abrasion, oxygen index, and hardness to obtain the following table:

[0077] Tensile strength: Tested according to the standard of GB / T 528-2009.

[0078] Elongation at break: Tested according to the standard of GB / T 528-2009.

[0079] Akron abrasion: Tested according to the standard of GB / T 1689-2014.

[0080] Oxygen index: Tested according to the standard of GB / T 2406-2009.

[0081] Hardness: Tested according to the standard of GB / T 531.1-2008.

[0082] Table 1 Performance of Flame-Retardant and Wear-Resistant NBR Masterbatch

[0083]

[0084] From Table 1, by comparing the performance of the flame-retardant and wear-resistant NBR masterbatch in Example 1, the flame-retardant and wear-resistant NBR masterbatch in Example 2, the flame-retardant and wear-resistant NBR masterbatch in Example 3, the flame-retardant and wear-resistant NBR masterbatch in Example 4, and the flame-retardant and wear-resistant NBR masterbatch in Example 5, it can be known that

[0085] In Example 1, the flame-retardant and wear-resistant NBR compound has the best performance, with excellent tensile strength, elongation at break, Akron abrasion, flame retardancy, and hardness, making it suitable for high-performance flame-retardant and wear-resistant parts;

[0086] In Example 2, the performance of the flame-retardant and wear-resistant NBR compound drops significantly, but it has the lowest cost and is suitable for occasions with low performance requirements;

[0087] In Example 3, the performance of the flame-retardant and wear-resistant NBR compound is close to that of Example 1, but the cost is lower, achieving the best balance between performance and cost;

[0088] In Example 4, the performance of the flame-retardant and wear-resistant NBR compound is slightly lower than that of Example 3, but the cost is further reduced, making it suitable for low-cost static flame-retardant products;

[0089] In Example 5, the performance of the flame-retardant and wear-resistant NBR compound is close to that of Example 2. Using too much mineral powder to replace talc powder results in lower performance;

[0090] It can be concluded that part of the talc powder can be replaced by mineral powder. The formulation in Example 3 is the best, achieving the best balance between performance and cost, with high cost performance. Other examples can be selected according to the application scenario. If there is too little data, several more groups can be made.

[0091] By using mineral powder to replace part of the talc powder as the filler of the flame-retardant and wear-resistant NBR compound, without affecting the performance of the flame-retardant and wear-resistant NBR compound, the production cost of the flame-retardant and wear-resistant NBR compound is significantly reduced. At the same time, the use of mineral powder can achieve resource utilization, with low heavy metal risk, meeting the environmental requirements of environmental protection and sustainable development. Mineral powder can improve the processing performance of the compound. The mineral powder particles are more regular, reducing the risk of sticking to the roll during mixing, increasing the fluidity of the rubber compound. The thermal conductivity of the mineral powder is better than that of talc powder, and the temperature during the internal mixing process is more stable. The compatibility between the mineral powder and carbon black is better, and the mixing time can be shortened by about 10%.

[0092] A preferred technical solution is that industrial waste can be used to replace the mineral powder, such as using fly ash to replace part of the talc powder, saving costs and realizing the reuse of industrial waste.

[0093] The above are only the preferred embodiments of the present invention, which are illustrative rather than restrictive to the present invention. Those skilled in the art understand that many changes, modifications, and even equivalents can be made within the spirit and scope defined by the claims of the present invention, but all will fall within the protection scope of the present invention.

Claims

1. A flame-retardant and wear-resistant NBR compound, characterized in that, It includes a rubber matrix, carbon black, fillers, plasticizers, and additives.

2. The flame-retardant and wear-resistant NBR compound according to claim 1, wherein, The rubber substrate is specifically nitrile rubber, and the additives are specifically flame retardants, vulcanizing agents, accelerators, and anti-aging agents.

3. The flame-retardant and wear-resistant NBR masterbatch according to claim 2, wherein The filler is specifically talc powder. The weight ratio of nitrile rubber is 65% - 75%, the weight ratio of carbon black is 18% - 25%, the weight ratio of talc powder is 12% - 18%, the weight ratio of plasticizer is 6% - 10%, the weight ratio of flame retardant is 5% - 8%, the weight ratio of vulcanizing agent is 1.5% - 2%, the weight ratio of accelerator is 1% - 1.5%, and the weight ratio of anti-aging agent is 1% - 1.5%.

4. A flame-retardant and wear-resistant NBR compound as claimed in claim 2, characterized in that, The filler is specifically ore powder. The weight ratio of nitrile rubber is 65% - 75%, the weight ratio of carbon black is 18% - 25%, the weight ratio of ore powder is 12% - 18%, the weight ratio of plasticizer is 6% - 10%, the weight ratio of flame retardant is 5% - 8%, the weight ratio of vulcanizing agent is 1.5% - 2%, the weight ratio of accelerator is 1% - 1.5%, and the weight ratio of anti-aging agent is 1% - 1.5%.

5. The flame-retardant and wear-resistant NBR masterbatch according to claim 2, wherein The filler is specifically a mixture of talc powder and ore powder. The weight ratio of nitrile rubber is 65% - 75%, the weight ratio of carbon black is 18% - 25%, the weight ratio of the mixture is 12% - 18%, the weight ratio of plasticizer is 6% - 10%, the weight ratio of flame retardant is 5% - 8%, the weight ratio of vulcanizing agent is 1.5% - 2%, the weight ratio of accelerator is 1% - 1.5%, and the weight ratio of anti-aging agent is 1% - 1.5%.

6. A preparation method of a flame-retardant and wear-resistant NBR compound, characterized in that, The preparation method is applied to the flame-retardant and wear-resistant NBR compound as described in claim 3, and includes the following steps: Step S1, Raw material preparation: Prepare the required nitrile rubber, carbon black, talc powder, plasticizer, flame retardant, vulcanizing agent, accelerator, and anti-aging agent according to the weight ratio. Step S2, Raw material pretreatment: Dry the talc powder to make its moisture content ≤ 0.5%, treat it with silane coupling agent KH-550 in a high-speed mixer for 10 minutes, and thin-pass the nitrile rubber 3 times on an open mill for plasticization. Step S3, First-stage mixing: In a mixer, adjust the rotation speed to 40 rpm, add the plasticized nitrile rubber and preheat it to 60°C, add the plasticizer and anti-aging agent, mix for two minutes, add the flame retardant, add the carbon black, mix until the power curve is stable, add the treated talc powder in two batches, discharge the rubber after mixing, press the masterbatch into a 5-mm-thick sheet, and store it at room temperature for 24 hours. Step S4, Second-stage mixing: On an open mill, adjust the roll gap to 1 mm and the roll temperature to 45°C, thin-pass the masterbatch 3 times, alternately add the vulcanizing agent and accelerator, mix for 5 minutes, adjust the roll gap to 2 mm, and turn and knead it in a triangular wrap 6 times, then take off the sheet after completion. Step S5, Quality inspection: Conduct physical property tests on the finished product, including tensile strength, flame retardancy, and wear resistance, to ensure that the material meets the requirements.

7. A preparation method of a flame-retardant and wear-resistant NBR compound, characterized in that, The preparation method is applied to the flame-retardant and wear-resistant NBR compound as described in claim 4, and includes the following steps: Step V1, Raw material preparation: Prepare the required nitrile rubber, carbon black, ore powder, plasticizer, flame retardant, vulcanizing agent, accelerator, and anti-aging agent according to the weight ratio. Step V2. Pretreatment of raw materials: The mineral powder is dried to make its moisture content ≤ 0.3%. It is modified with titanate coupling agent NDZ-201 in a high-speed mixer for 10 minutes. The nitrile rubber is passed thinly through an open mill 3 times for plasticizing. Step V3. First-stage mixing: In an internal mixer, adjust the rotation speed to 40 rpm and the initial temperature to 60 °C. Add the plasticized nitrile rubber and preheat it to the state of wrapping around the roll. Add the plasticizer and antioxidant, mix for two minutes, then add the flame retardant and carbon black, and mix until the power curve is stable. Add the treated mineral powder in two batches, discharge the mixture after mixing, press the masterbatch into a sheet with a thickness of 5 mm, and let it stand at room temperature for 24 hours. Step V4. Second-stage mixing: In an open mill, adjust the roll gap to 1 mm and the roll temperature to 45 °C. Pass the masterbatch thinly through the mill 3 times, alternately add the vulcanizing agent and accelerator, mix for 6 minutes, adjust the roll gap to 2 mm, and turn it over by triangular wrapping 6 times. Then take off the sheet after completion. Step V5. Quality inspection: Conduct physical property tests on the finished product, including tensile strength, flame retardancy, and abrasion resistance, to ensure that the material meets the requirements.

8. A preparation method of a flame-retardant and wear-resistant NBR masterbatch, characterized in that, The preparation method is applied to the flame-retardant and wear-resistant NBR masterbatch as described in Claim 5, and includes the following steps: Step N1. Preparation of raw materials: Prepare the required nitrile rubber, carbon black, talcum powder, mineral powder, plasticizer, flame retardant, vulcanizing agent, accelerator, and antioxidant according to the weight ratio. Step N2. Pretreatment of raw materials: The talcum powder is dried and treated with silane coupling agent KH-550 in a high-speed mixer for 10 minutes. The mineral powder is dried and modified with titanate coupling agent NDZ-201 in a high-speed mixer for 10 minutes. The nitrile rubber is passed thinly through an open mill 3 times for plasticizing. Step N3. First-stage mixing: In an internal mixer, adjust the rotation speed to 40 rpm and the initial temperature to 60 °C. Add the plasticized nitrile rubber and preheat it to the state of wrapping around the roll. Add the plasticizer and antioxidant, mix for two minutes, then add the flame retardant and carbon black, and mix until the power curve is stable. Add the mixture of talcum powder and mineral powder in two batches, discharge the mixture after mixing, press the masterbatch into a sheet with a thickness of 5 mm, and let it stand at room temperature for 24 hours. Step N4. Second-stage mixing: In an open mill, adjust the roll gap to 0.8 mm and the roll temperature to 45 °C. Pass the masterbatch thinly through the mill 3 times, alternately add the vulcanizing agent and accelerator, mix for 5 minutes, adjust the roll gap to 2 mm, and turn it over by triangular wrapping 6 times. Then take off the sheet after completion. Step N5. Quality inspection: Conduct physical property tests on the finished product, including tensile strength, flame retardancy, and abrasion resistance, to ensure that the material meets the requirements.

Citation Information

Patent Citations

  • Flame-retardant wear-resistant NBR mixed rubber for conveyer belt covering layers, and preparation method thereof

    CN110643089A